PENDEKATAN PARIWISATA BERKELANJUTAN PADA INDUSTRI KERAJINAN TENUN SUKARARA LOMBOK TENGAH - Dhony Hermanto; Nurul Ismillayli; Baiq Handayani Rinuastuti; Ulul Khairi Zuryati; Fahrurazi Fahrurazi; Ahmad Wirahadi; Handa Muliasari (Universitas Mataram, 2022)
Sukarara Village as a weaving center village in Lombok is expected to be one of the attractions for tourists visiting Lombok. Weaving skills are passed down from generation to generation to the women of Sukarara Village so that they are able to produce very good quality woven fabrics. The management of the Sukarara weaving tourism village is under the coordination of the Kelompok Sadar Wisata (Pokdarwis) Subahnale, especially the marketing of woven fabrics. Unfortunately, their knowledge and business management skills are still limited so they require assistance and training to have good management knowledge in terms of production, human resources, finance and marketing as a form of community service activities (PKM). PKM activities are carried out through outreach and training to partners, starting with a survey of partner conditions (through FGDs and interviews), then business management training (production, human resources, marketing and finance) and evaluating partner knowledge based on test scores. Partners are also introduced to SWOT analysis in order to evaluate the condition of the business so that it keep going and growing. The evaluation results showed that the implementation of socialization and training by the PKM team in general has been running quite effectively. This is indicated by the increase in the average score of partners' knowledges of business management including production, human resources, finance and marketing. The active involvement and enthusiasm of the participants were observed during the activity. The sustainability of this program needs to be pursued by Pokdarsis Subahnale while still receiving direction from the PKM implementation team so that the role of Sukarara Village as a weaving tourism village is more apparent in improving the welfare of its people.